Economic Evaluation of Sacituzumab Govitecan for the Treatment of Metastatic Triple-Negative Breast Cancer in China and the US - Chen, Jigang; Han, Mingyang; Liu, Aihua; Shi, Bo (Frontiers in Oncology, 2021)
Background: The effectiveness of Sacituzumab Govitecan (SG) for metastatic triple-negative breast cancer (mTNBC) has been demonstrated. We aimed to evaluate its cost-effectiveness on mTNBC from the Chinese and United States (US) perspective. Methods: A partitioned survival model was developed to compare the cost and effectiveness of SG versus single-agent chemotherapy based on clinical data from the ASCENT phase 3 randomized trial. Cost and utility data were obtained from the literature. The incremental cost-effectiveness ratio (ICER) was measured, and one-way and probabilistic sensitivity analyses (PSA) were performed to observe model stability. A Markov model was constructed to validate the results. Results: In China, SG yielded an additional 0.35 quality-adjusted life-year (QALY) at an additional cost of Chinese Renminbi ¥2257842. The ICER was ¥6375856 (924037)/QALY. In the US, SG yielded the same additional QALY at an extra cost of 175393 and the ICER was 494479/QALY. Similar results were obtained from the Markov model. One-way sensitivity analyses showed that SG price had the greatest impact on the ICER. PSA showed the probability of SG to be cost-effective when compared with chemotherapy was zero at the current willing-to-pay threshold of ¥217341/QALY and 150000/QALY in China and the US, respectively. The probability of cost-effectiveness of SG would approximate 50% if its price was reduced to ¥10.44/mg in China and 3.65/mg in the US. Conclusion: SG is unlikely to be a cost-effective treatment of mTNBC at the current price both in China and the US.